8(x-6)=-3(6-2x)+5x

Simple and best practice solution for 8(x-6)=-3(6-2x)+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-6)=-3(6-2x)+5x equation:



8(x-6)=-3(6-2x)+5x
We move all terms to the left:
8(x-6)-(-3(6-2x)+5x)=0
We add all the numbers together, and all the variables
8(x-6)-(-3(-2x+6)+5x)=0
We multiply parentheses
8x-(-3(-2x+6)+5x)-48=0
We calculate terms in parentheses: -(-3(-2x+6)+5x), so:
-3(-2x+6)+5x
We add all the numbers together, and all the variables
5x-3(-2x+6)
We multiply parentheses
5x+6x-18
We add all the numbers together, and all the variables
11x-18
Back to the equation:
-(11x-18)
We get rid of parentheses
8x-11x+18-48=0
We add all the numbers together, and all the variables
-3x-30=0
We move all terms containing x to the left, all other terms to the right
-3x=30
x=30/-3
x=-10

See similar equations:

| 4r-5=90 | | 40+1.50x=30 | | 12x+13=2x+93 | | 9-4(2x-1)=1-5x | | 27-7b=-6-2(1+6b) | | 42+x=-1 | | 703x+10=100 | | 3x+1/6-3x+1/42=7 | | -10x-(-5-3x=-3(4x-2) | | 4m+6=71 | | p−839=1 | | 2x-6x=-3-2-2 | | -20-8+10c=13c+20 | | x(3x+4)(x-7)=0 | | −35y−8=−33y+22 | | 7x+16+8x+12+9x+8=0 | | .10x+x=136000 | | 12x+13=2x+8+85 | | 5x–12=122 | | 7/8y-4=9 | | b+7-4bb=3 | | –6j=5−6j | | 3(a+3)=2 | | -4(n+1)=3(1-n) | | 50+1.50x=40 | | x-x-6x=-3-2-2 | | 3d+10=5d+2d | | 11m-12.4=14.39+12.9m | | 8a^2-16a-92=0 | | -1+n+3+6=3+4n-4n | | 8x-77=180 | | 7v-28=8+3v |

Equations solver categories